Analisis Etika Ibnu Miskawaih terhadap Fenomena ‘Flexing’ di Media Sosial - Budiman, Arip Budiman (CV Kalimasada Group, 2023)
This research aims to explore the relevance of Ibn Miskawaih's ethics in examining the phenomenon of flexing considered inconsistent with Islamic teachings, particularly the behavior of showing off (riya). The flexing phenomenon has emerged with the influence of social media, encouraging people to display and seek recognition, especially from those who appear super-wealthy. The research problem formulation identifies whether there is a relevance of Miskawaih's ethics in examining flexing behavior. Qualitative research methodology with a literature review approach is employed to analyze Miskawaih's ethical concepts and flexing behavior. The research findings indicate a relevance between Miskawaih's ethical concepts, especially simplicity and balance, and flexing behavior reflecting the desire to appear exclusive and superior. The results and discussion of this research demonstrate that in the social media context, Miskawaih's ethical concepts such as simplicity and balance are relevant in assessing flexing behavior, which often reflects a drive to appear exclusive, impressive, or superior. The conclusion asserts that the analysis of Miskawaih's ethics provides insights into the flexing phenomenon by highlighting the inconsistency of such behavior with Islamic ethical values. Suggestions for future research include integrating psychological and sociological dimensions, understanding individual motivations behind flexing, examining the impact on psychological well-being, and exploring the relationship with information technology developments. There is also a need for the development of prevention strategies and public education to adhere to Miskawaih's ethical values in the era of social media.